2019
DOI: 10.1002/cbic.201900633
|View full text |Cite
|
Sign up to set email alerts
|

5‐Benzylidene‐4‐Oxazolidinones Are Synergistic with Antibiotics for the Treatment of Staphylococcus aureus Biofilms

Abstract: The failure of frontline antibiotics in the clinic is one of the most serious threats to human health and requires a multitude of novel therapeutics and innovative approaches to treatment so as to curtail the growing crisis. In addition to traditional resistance mechanisms resulting in the lack of efficacy of many antibiotics, most chronic and recurring infections are further made tolerant to antibiotic action by the presence of biofilms. Herein, we report an expanded set of 5‐benzylidene‐4‐oxazolidinones that… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Our data are consistent with a role for TolC-mediated drug efflux in S. Typhimurium resistance to the compound. In addition to potent growth inhibition, some analogs have antibiofilm effects on S. aureus at sub-MICs as we found for S. Typhimurium (18,19). The high concentration of JJM-ox-3-70 needed to reduce S. Typhimurium biofilm makes it an unlikely candidate for development as treatment for Gram-negative biofilm-mediated infections.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Our data are consistent with a role for TolC-mediated drug efflux in S. Typhimurium resistance to the compound. In addition to potent growth inhibition, some analogs have antibiofilm effects on S. aureus at sub-MICs as we found for S. Typhimurium (18,19). The high concentration of JJM-ox-3-70 needed to reduce S. Typhimurium biofilm makes it an unlikely candidate for development as treatment for Gram-negative biofilm-mediated infections.…”
Section: Discussionmentioning
confidence: 80%
“…In spite of their good antimicrobial efficacy against methicillinresistant strains of Staphylococcus aureus, these compounds fail to inhibit growth of Gram-negative organisms (16,17). In addition to their antimicrobial effects, some analogs have antibiofilm properties at sub-MICs (18) or can be utilized as adjuvants with existing antimicrobials (19). Understanding how the 4-oxazolidinone analogs may alter biofilm formation will allow us to create analogs with improved efficacy.…”
mentioning
confidence: 99%
“…With the ability of synoxazolidinone natural product analogues (5‐benzylidene‐4‐oxazolidinones) to disperse biofilms established, Pierce and co‐workers [137] demonstrated that related analogues, such as the formaldehyde hemiaminal of the oxazolidine core 15, work synergistically with antibiotics such as doxycycline (reducing the antibiotic's MBEC) to eradicate pre‐formed S. aureus ATCC 29213 biofilms. Subsequently, Pierce and colleagues [138] examined the activity of the 4‐oxazolidinone analogue JJM‐ox‐3‐70 (16) against the gram‐negative pathogen Salmonella typhimurium .…”
Section: ‐Oxazolidinones With Anti‐biofilm Activitymentioning
confidence: 99%
“…(C) MIC, MBEC, and synergy activity of 59 reported against ATCC BAA 44. The images at the right are reproduced with permission from ref . Copyright 2019 Wiley-VCH.…”
Section: Synoxazolidinone Natural Productsmentioning
confidence: 99%
“…During these efforts we also serendipitously prepared the formaldehyde hemiaminals of the oxazolidine core (57−59; Figure 4B) and found these compounds to have improved activity, although their lifetimes in cell culture remain unknown. 3 At this stage, we evaluated our lead compounds for their ability to eradicate preformed robust biofilms in combination with existing antibiotics. To our delight, compounds such as 59 were extremely effective at clearing biofilms and were synergistic with antibiotics such as doxycycline, reducing the antibiotics' minimal biofilm eradication concentration (MBEC) to just 16 μg/mL with only 8 μg/mL oxazolidinone 59 (Figure 4D).…”
Section: ■ Introductionmentioning
confidence: 99%